2018
DOI: 10.1007/s00705-018-3893-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll-like receptor 3 and Toll-like receptor 9 single-nucleotide polymorphisms with hepatitis C virus persistence among Egyptians

Abstract: Toll-like receptors (TLRs) give the innate immune system a considerable specificity for a large range of pathogens. TLR3 detects dsRNA of viruses while TLR9 recognizes bacterial and viral unmethylated CpG motifs. This study examined whether there is a potential association between single-nucleotide polymorphisms (SNPs) in the TLR3.rs3775290 (c.1377C/T), TLR9.rs5743836 (-1237T→C) and TLR9.rs352140 (G2848A) genes and HCV infection among Egyptian patients and healthcare workers (HCWs). We enrolled 546 subjects (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…The high serum level of IL-6 had a predictive function in the pathogenesis of insulin resistance and cardiac complications in patients with diabetes. [26][27][28][29][30][31] Also, Cheng et al 32 found that increased plasma concentrations of resistin were strongly associated with subsequent development of heart failure. The association of resistin with heart failure persisted after adjustment for established heart failure risk factors, obesity, markers of insulin resistance and inflammation, and concentrations of NT-proBNP, and after exclusion of prevalent and incident CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The high serum level of IL-6 had a predictive function in the pathogenesis of insulin resistance and cardiac complications in patients with diabetes. [26][27][28][29][30][31] Also, Cheng et al 32 found that increased plasma concentrations of resistin were strongly associated with subsequent development of heart failure. The association of resistin with heart failure persisted after adjustment for established heart failure risk factors, obesity, markers of insulin resistance and inflammation, and concentrations of NT-proBNP, and after exclusion of prevalent and incident CHD.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the TLR-3.rs3775290 'CC' genotype was associated with HCV chronicity, and that the TLR-9 gene played no major role in this infection [14]. This study identified the role of TLR-3.rs3775290 (c.1377C/T), TLR-9.rs5743836 (−1237T→C) and TLR-9.…”
Section: Introductionmentioning
confidence: 74%
“…Mosaad et al ( 2019 ) showed that the heterozygous CT genotype of TLR3rs 3775290 appeared to be a susceptibility risk factor of chronic HCV infection, while the homozygous CC and of TLR7rs 179008, TLR9rs 352140 single nucleotide polymorphism (SNPs), including the combined genotype (CC-AT-GA) were protective. Earlier, another group of authors (Hamdy et al 2018 ) found that the TLR3rs 3775290, “CC” genotype was associated with chronic HCV infection, this SNP, however, did not correlate with the HCV RNA load of the chronic subjects. These studies indicate the potential value of genetic exploration of TLRs in this disease, in spite of evident discrepancies between individual reports.…”
Section: Viral Hepatitismentioning
confidence: 93%